The Relevance of Crude Oil Prices on Natural Gas Pricing Expectations: A Dynamic Model Based Empirical Study - Salles, Andre Assis de; Campanati, Ana Beatriz Mendes (International Journal of Energy Economics and Policy, 2019)
The natural gas price is an important and often decisive variable for economic policy makers. Many studies have been developed in order to establish a stochastic process that can represent the movements or the returns of natural gas prices or variations of such prices time series to forecast price expectations. This work aims to study the relationship between natural gas and crude oil prices in the international market, proposing to investigate its nature and long term equilibrium, through the development of adequate econometric models for determining future expectations of major natural gas price benchmarks, or of their returns. In order to accomplish this, time series for both benchmark crude oil and natural gas prices are subjected to statistical tests with the purpose of verifying the underlying hypotheses behind the appropriate autoregressive dynamic models. The conditional heteroskedasticity and non-normality of the return series, which are prevalent characteristics in energy markets, are considered when elaborating these models. To reach the purpose of this work weekly natural gas and crude oil prices benchmarks traded in the international market were collected. Keywords: Natural Gas Prices; Crude Oil Prices; Cointegration; Causality; ARDL Model. JEL Classifications: C22; C51; G15; Q40 DOI: https://doi.org/10.32479/ijeep.7755